Interaksi Sosial Komunitas Islam Aboge Dengan Masyarakat Desa Cikakak Kecamatan Wangon Kabupaten Banyumas - Sa'dudin, Ihsan; Riza Chamadi, Muhamad; Munasib, Munasib; Achmad, Fathoni; Zayyadi, Ahmad (Universitas Muhammadiyah Magelang, 2019)
The religious practice of a small part of the village community in Banyumas Regency that adheres to the flow of beliefs and teachings of puritarianism tends to be exclusive. One of them is a Muslim aboge. This can create an interactive gap with rural communities in general. On the other hand, the existence of this community still exists and lives in the development of the digital era. This research was conducted to answer two things; first, the concept of defense of the existence of the culture and teachings of the Islamic community aboge in the digital era; secondly, the forms of social interaction carried out by Muslim communities aboge with the people of the Cikakak Wangon Banyumas Village. This research is a field study located in Cikakak Village, Wangon District, Banyumas Regency with a phenomenology approach. Methods in data search using interviews and documentation compiled and reported descriptively. After going through the research stage, there are at least three points that can be concluded, namely: 1) The social interaction of the Aboge community with the Cikakak Village community in Wangon Subdistrict Banyumas Subdistrict takes place dynamically, functionally, and has a specific purpose, 2) The Islamic Community Aboge is no different from surrounding communities, and 3) the Aboge Islamic community makes ghair mahdah worship a means of interaction with other communities.